New data on family Araneidae from district Swat with updated checklist of the family from Pakistan - Ullah,I. (2024)
Abstract The aims of the present research was to find out the diversity of family Araneidae in district Swat Pakistan and to provide updated checklist of the family Araneidae from Pakistan. Also their occurrence throughout the year was given from District Swat Khyber Pakhtunkhwa, Pakistan. Data was collected from January 2018 to December-2018 from seven different Tehsils of District Swat by using different methods like pitfall trap, ground hand collection, air hand collection and were then preserved in plastic vials and appendorf tubes by using 70% ethanol. Camera mounted on microscope was used for photography. By using literature from World Spider Catalog, 2022, spiders were identified to species level. In a ttal of 1243 specimens of family Araneidae 4 genera and 7 species were identified. Dominant species with great number of specimen collected was Cyrtophora citricolla with 229 (18.4%) samples, followed by Bojaranius mitificus (15.7%), Neoscona Scylla (15.4%), Argiope lobata (14.8), Neoscona theisi (14.6%) and Neoscona polyspinippes (13.8%) respectively. While lowest collection was done of Argiope versicolor with 90 (7.3%) samples. High occurrence of spiders was studied during July 187 samples. Fluctuation in temperature can affect the diversity of spiders observed and recorded in present study with lowest collection done in low temperature. Moreover, the humidity also play a great role in spiders’ population and occurrence.